Examining Customer Adoption and Usage of Plastic Money in Kathmandu Valley - Lawaju, Purnima; Shrestha, Sujan; Basyal, Devid Kumar; Shrestha Lacoul , Sanjana; Paudel, Udaya Raj; Thakur, Abhishek (Journal of Business and Management, 2024)
Background: Plastic money and virtual wallets are becoming increasingly popular due to their adaptability and convenience. Plastic money is becoming accepted everywhere as the world becomes more globalized with changing consumer behavior Objectives: This purpose of the study is to investigate the overall perception of plastic money among customers in Kathmandu Valley. It seeks to uncover the factors influencing users’ attitudes, pinpoint the challenges encountered by plastic money users, and evaluate managerial strategies for enhancing the utilization of plastic money. Methods: This study employs an explanatory research design. It considers customers using plastic money in Kathmandu Valley as the population and selects a sample of 404 using the convenience sampling method to analyze customer acceptance and use of plastic money. The questionnaire is self-administered and adapted from various sources. The data is analyzed both using MS-Excel and SmartPLS 4.0. Results: Findings show that behavioral intention, which in turn strongly predicts how people would utilize plastic money, is significantly influenced by effort anticipation, social influence, and habit. It is discovered that hedonic drive and perceived expectation are not very good indicators of behavioral intention. Conclusion: Effort expectancy, social influence and habit needs to be managed to enhance the people’s behavioral intention which will have impact on use behavior of plastic money. Some of the challenges while using plastic money are lack of availability of technology, lack of knowledge and expertise which can be minimized by increasing availability of technology and clear information.